The role of custom in establishing family security (مجلة الواحات للبحوث والدراسات, 2026)
This research explores the concept of custom as one of the influential factors in family life, highlighting its impact on achieving family security, especially in light of the social and cultural transformations occurring in contemporary societies. Family security is considered one of the most essential pillars of social stability, as it is closely linked to the stability of the marital relationship, child care, and the regulation of family interactions based on specific values and norms. The study includes a definition of custom and its conditions, as well as an explanation of the concept and importance of family security. It then analyzes the role of custom in reinforcing the economic, psychological, social, and intellectual foundations of family security. The research concludes that custom is a significant factor in strengthening family security—provided it aligns with the spirit and objectives of Islamic legislation. Furthermore, family security is regarded as one of the key components of overall social security.